Morphometric Analysis of Mandibular Ramus for Sex Determination on Orthopantomogram - Shakya, Tripti; Maharjan, Anjana; Pradhan, Leeza (Journal of Nepal Health Research Council, 2022)
Background: Mandible is the strongest and most dimorphic bone of skull which resists postmortem changes and plays an important role in sex determination. Skeletal characteristic differ in different population therefore need of population specific studies. The aim of present study was to determine sex by morphometric analysis of mandibular ramus. Methods: A cross sectionalstudy was performed in orthopantomogram of patients collected from Dental Department of Patan Hospital, Lalitpur, Nepal. One hundred and fifty digital orthopantomogram of patient fulfilling inclusion criteria were included in the study. Five different mandibular parameters (maximum ramus breadth, minimum ramus breadth, condylar height/maximum ramus height, projective height of ramus, and coronoid height) were measured bilaterally resulting in total 300 rami being assessed. Orthopantomogram were made with Planmeca ProMax classic 2D machine and all the measurements on digital radiograph were performed with Planmeca Romexis viewer software version 5.1.0.R. Discriminant function analysis was performed to find the most significant predictors for determining sex. Results: All the measured mandibular parameters were statistically significantly higher in male than females (P<0.001). Condylar height was the most significant predictors for determining sex. The discriminate function equation was derived to determine sex with an overall accuracy of 84.0%. Conclusions: Morphometric analysis of mandibular ramus using digital orthopantomogram showed a high sexual dimorphism. Keywords: Discriminant function analysis; mandibular ramus; orthopantomogram; sexual dimorphism.